PERTUMBUHAN DAN HASIL TANAMAN JAGUNG MANIS (ZEA MAYS SACCHARATA STURT) AKIBAT PEMBERIAN DOSIS PUPUK MAJEMUK NPK - Solihin, Eso; Sudirja, Rija; Yuniarti, Anni (AGRO TATANEN | Jurnal Ilmiah Pertanian, 2024)
Sweet corn (Zea mays saccharata Sturt) is one of the food crops that is needed to meet food needs. Efforts to increase the quantity and quality of sweet corn can be done through fertilization. To ensure that sweet corn's nutritional requirements for nitrogen (N), phosphorus (P) and potassium (K) are met, fertilizer such as NPK can be applied. This research aims to analyze the effect of various doses of NPK fertilizer on the growth and yield of sweet corn. The research was carried out at the Ciparanje Experimental Garden, Faculty of Agriculture, Padjadjaran University, Jatinangor, Sumedang, from November 2023 to March 2024. The research used a Complete Randomized Block Design (RAK) with ten treatments and three replications. The treatments given include: Control (without N, P, K), Standard N, P, K (Urea, SP-36, and KCl), and NPK fertilizer with varying doses (¼, ½, ¾, 1, 1 ¼, 1 ½ , 1 ¾, and 2). The research results showed that the application of NPK compound fertilizer had a significant effect on growth parameters, yield components and sweet corn yield. Meanwhile, the most effective dose in increasing plant yields was H treatment (1 ½ doses of NPK).